A methods engineering study on Lincophil Aluminum Manufacturing Corporation - Balanza, Nathaniel Eric.; Balois, Stephanie; Caw, Eunice; Perez, Maria Selina (Diliman, Quezon City College of Engineering, 2002)
"Durable, stylish, economical", these qualities best describe the products made by LincoPhil Aluminum Manufacturing Corporation, a company that is considered as one of the leading manufacturers of aluminum kitchenware and baking products in the country. Carrying the brands "Bell" and "Universal". LincoPhil's lines of products are found on every kitchenware section of almost all department stores and supermarkets nationwide. Among its clients are Shoemart, Isetann, Plaza Fair, and Gaisano Malls in Visayas and Mindanao. Their production plant is located in Sterling Industrial Park in Meycauayan, Bulacan while their office is located in G. Araneta Avenus, Quezon City. By applying concepts in Methods Engineering and other tools, this study aims to implement some changes in the company's production system that would help increase their productivity and efficiency. The study was able to determine the company's main problem and propose solutions to reduce, if not eliminate this. Using the different analytical tools, it was found that the main problem was Lincophil's inability to meet a customer demands as prompt as its competitors for the year 2001 because of its low level of output. Two root causes were addressed in this study, namely, the spinning machines can only produce up to 300 finished products daily, and the plant has poor layout. Using Work Sampling, Productivity Indices, Statistical, Cost Benefit Analysis and Linear Programming, the solution to the first problem was determined. The proposed solution is for Lincophil to purchase a second hand double action hydrauilic machine to increase output and also improve the quality of their products. The problem regarding poor plant layout was solved using Facility Layout Planning. It was found that to be able to solve this problem, the warehouse door that is kept closed must be opened and the Packaging Area and Finishing Area be moved to the lower right side of the Warehouse and the Storage Area for Delivery should be placed near the door of the Warehouse. Transportation distances of the products within the factory is reduced considerably and the crossing paths causing traffic is also decreased with this alternative. The group recommends that LincoPhil consider buying more riveter to improve their handle attachment and rearrange their storage racks further apart to improve their storage system. Further studies may concentrate on developing an inventory system to facilitate the retrieval of stored goods.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis